Pendampingan Pengisian Aplikasi Data Pokok Pendidikan Pada Operator Sekolah Di Tk Aisiyah Bustanul Athfal 6 - Lestari, Bekti Wiji; Rawi, Rais Dera Pua; Wangsi, Mitta Muthia; Waly, Nur Aeni; Bintari, Wisang Candra (Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
This training aims to provide assistance in filling out basic education data applications which are useful for the ‘Aisyiyah Bustanul Athfal 6 Aimas Kindergarten school. This study uses qualitative data. From the results of the study, it shows that the purpose of this service activity has been achieved, this can be seen from the operators who are very understanding regarding filling out the dapodik application including filling in school data, teachers and education staff and student data correctly (see Figure 5). Filling in the data on the dapodik application provides benefits for the school, including the ease of getting information about schools and public trust in sending their children to study at ‘Aisyiyah Bustanul Athfal 6 Aimas Kindergarten.